The Efficacy and Safety of Docetaxel Plus Prednisone with or without Lenalidomide in Patients with Castrate-Resistant Prostate Cancer: The MAINSAIL Trial - Vinall, Phil (MD Conference Express, 2012)
Lenalidomide, has been used to treat myeloma and myelodysplastic syndrome. This article reports on results from the Study to Evaluate Safety and Effectiveness of Lenalidomide in Combination with Docetaxel and Prednisone for Patients with Castrate-Resistant Prostate Cancer [MAINSAIL; NCT00988208] trial, which showed that the addition of lenalidomide to docetaxel and prednisone did not improve overall survival in castrate-resistant prostate cancer patients and its use was associated with greater toxicity.